The impact of comprehension of disease-related information and perceptions regarding effects and controllability on protective and social solidarity behaviors with regard to COVID-19 - KAVŞUR, ZEYNEP (SPRINGER HEIDELBERG, 2020)
Aim The main theme in health behavior theories is that risk perception goes hand in hand with knowledge of the disease, perceived effects, and perceived controllability of the disease. This study aims to investigate the impact of all those variables on protective and social solidarity behaviors concerning COVID-19. Subject and methods This cross-sectional study was conducted in the early stages of the outbreak in Turkey. Data were collected between April 1 and April 6, 2020, via an online survey. The reliability of the scales was tested. Exploratory factor analysis was used to examine construct validity. SEM analysis was employed to determine the model. Results SEM analysis indicates that fit indices (chi 2 = 4.108 df = 2; chi 2/df = 2.05; RMSEA = 0.04; CFI = 0.99; GFI = 0.99; PCLOSE = 0.545) were good model fits. The structural analysis indicated that the comprehensibility of information, perceived effects and controllability of the disease, and social solidarity had a statistically significant direct positive effect on protective behavior (beta = 0.133,p < 0.001; beta = 0.399,p < 0.001; beta = 0.084,p < 0.001; beta = 0.171,p < 0.001, respectively). Conclusion A health behavior model in the literature was evaluated with the data for a society facing a pandemic risk, and it was shown that the data fit the model perfectly. The study has revealed that understanding the information about COVID-19 increases social solidarity. Most importantly, it is concluded that social solidarity increases society's protective behaviors. Participants did not find COVID-19-related information to be comprehensible. Despite disease uncertainty in the early stage of the pandemic, participants had a high perception of the severity of COVID-19.
Keywords: Health behavior; Perceived severity; Perceived control; Protective behavior; COVID-19 knowledge; Social solidarity; RISK; TRANSLATION; SARS